2022
DOI: 10.3390/en15217889
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Carbonated Engineered Water as EOR Solution for Oil-Wet Carbonate Formation

Abstract: Carbonated water has proven advantages over conventional CO2 injection in terms of arresting free CO2 mobility, low-pressure injection, lower volume requirement, and higher efficiency. The term “engineered water” is designated to selective ion-spiked injection water with the advantage of the ion-exchange reactions with the rock minerals and releasing trapped oil. This article investigated the synergic effect of dissolved CO2 and engineered water for oil recovery and understanding inner mechanisms. Recovery eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…They indicated that carbonated engineered seawater significantly influenced the pore size distribution and cumulative porosity of carbonate cores. For moderately high-permeability rock samples (20.25 mD), the cumulative porosity increased from 20.45% to 22.76% . The high dissolution of carbonate minerals, predominantly calcite, is responsible for this observation.…”
Section: Consequence Of Geochemical Processes During Cwimentioning
confidence: 88%
See 4 more Smart Citations
“…They indicated that carbonated engineered seawater significantly influenced the pore size distribution and cumulative porosity of carbonate cores. For moderately high-permeability rock samples (20.25 mD), the cumulative porosity increased from 20.45% to 22.76% . The high dissolution of carbonate minerals, predominantly calcite, is responsible for this observation.…”
Section: Consequence Of Geochemical Processes During Cwimentioning
confidence: 88%
“…For moderately high-permeability rock samples (20.25 mD), the cumulative porosity increased from 20.45% to 22.76%. 141 The high dissolution of carbonate minerals, predominantly calcite, is responsible for this observation. These findings align with earlier studies.…”
Section: Mineral Trappingmentioning
confidence: 99%
See 3 more Smart Citations